Experimental Optimization of Using Natural Pozzolan in Chloride Ion Exposed Concrete via Taguchi Method - Behshad, Amir (Array, 2021)
Concrete durability is one of the most important concerns in the field of construction. The environmentally friendly materials that can provide the durability are of great value in the construction of concrete structures. The use of natural pozzolans is one of the cheapest and most efficient methods in this field, which offers a good performance from environmental and economic point of view and satisfies required engineering parameters. In this study, the effect of using natural pozzolan in the manufacture of concrete exposed to sulfate and chloride ion of Oman sea water was investigated. The Taguchi optimization method was used to reduce the number of samples prepared, reduce the cost of experiments and achieve an optimal mix design. The four parameters, namely water to cement ratio, different percentages of natural pozzolan, super-plasticizer and cement grade with different ratios, were considered as problem variables. The Taguchi optimization method proposed 8 mix designs based on the defined levels for the variables. By constructing 96 samples, two parameters of permeability and water absorption from Oman Sea and drinking water were investigated in the samples. By introducing the results of the experiments into the Taguchi method, the final optimal design was presented by this method, and by constructing 12 additional samples and conducting permeability and water absorption experiments, the behavior of this optimal mix design was verified. The appropriate performance of the Taguchi method was demonstrated by obtaining the optimal mix designs from the Taguchi method, constructing this mix design and comparing the results with the regulation limitations. The results showed that it is acceptable to use natural pozzolan under moderate to severe chloride and sulfate ion attacks, but it is not recommended in the extreme environmental conditions.